2020
DOI: 10.1111/imj.14323
|View full text |Cite
|
Sign up to set email alerts
|

Get with the guidelines: management of chronic obstructive pulmonary disease in emergency departments in Europe and Australasia is sub‐optimal

Abstract: Background Exacerbations of chronic obstructive pulmonary disease (COPD) are common in emergency departments (ED). Guidelines recommend administration of inhaled bronchodilators, systemic corticosteroids and antibiotics along with non‐invasive ventilation (NIV) for patients with respiratory acidosis. Aim To determine compliance with guideline recommendations for patients treated for COPD in ED in Europe (EUR) and South East Asia/Australasia (SEA) and to compare management and outcomes. Methods In each region, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 20 publications
(25 reference statements)
0
26
0
Order By: Relevance
“… 8 A planned substudy of AANZDEM concluded compliance with COPD evidence-based guidelines is suboptimal in EDs and suggested further research is required to improve compliance with care based on published guidelines. 18 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 8 A planned substudy of AANZDEM concluded compliance with COPD evidence-based guidelines is suboptimal in EDs and suggested further research is required to improve compliance with care based on published guidelines. 18 …”
Section: Introductionmentioning
confidence: 99%
“… 26 Exploring the barriers and enablers for interdisciplinary team members to provide holistic care as per COPD guidelines (medical, physical, psychological, social, spiritual and palliation) is crucial. 18 27 Interdisciplinary care has proven to significantly optimise functionality and prevent deterioration in patients with COPD, which subsequently reduces hospital admissions and hospital days per person. 16 21 Initiation of consistent interdisciplinary healthcare interventions for patients with COPD will extrude any implementation gap and prevent readmissions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 COPD guidelines non-adherence in both pharmacological and non-pharmacological management is well-recognised and is a reported phenomenon in national and international literature. [10][11][12] A COCHRANE systematic review on integrated disease management programs for COPD reported improved disease-related quality of life, increased exercise capacity, reduced hospital admissions and hospital days per person. 13 Sub-optimal dissemination and implementation impede adoption into clinical practice by interdisciplinary health professionals.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 However, worldwide research reports lack of COPD guideline adherence. 11,[18][19][20][21][22] Implications of guidelines non concordanceare repetitive readmissions with COPD exacerbations, increased economic burden, and poor optimisation of lung function and overall health. 12,23,24 This systematic review set out to identify known contributing factors towards COPD guidelines nonadherence from the time of admission to hospital to time of discharge.…”
Section: Introductionmentioning
confidence: 99%